FRINGE BENEFITS OF DIGITAL TECHNOLOGY IN LEARNING AND TEACHING SPEAKING AND LISTENING ENGLISH (International Journal of Food and Nutritional Sciences, 2019)
This Paper enlightens on the area how children gaining the skills they will need for their future education and careers are growing up in a supportive digital environment. Here are some great tech-based English-practice activities you can do with your youngster. Children have numerous possibilities to practice their English thanks to digital technologies. Teachers claim that the usage of technology significantly affects students' learning of a second language. Positive feedback is more prevalent, despite some professors displaying detrimental effects of contemporary technologies on grabbing students' attention. Teachers gave examples of how using technology into teaching and learning promotes students' interest in learning second language. The use of Digital Technology which makes easy in teaching and learning the targeted language. The English language teachers are facing many challenges to make the English class more interesting to the students. Most of the teachers have very low level of knowledge in the usage of ICT. It is a good opportunity to both teachers and students in exploring their level of understanding of Digital Technology. Both are equally beneficial of modern technologies rather than choosing repeated traditional methods in teaching and learning process.